A "Jail Escape Technique" (JET) for distal side branch wiring during provisional stenting: Feasibility and first‐in‐man study. (1st November 2017) - Xiao, Han; Chen, Shengda; Wang, Guixue; Du, Ruolin; Song, Yaoming; Jin, Jun; Huang, Lan; Jabbour, Richard; Azzalini, Lorenzo; Zhao, Xiaohui
Abstract : Objective: To evaluate the feasibility of a novel technique for achieving distal SB access and improve strut apposition during provisional stenting. Background: While distal rewiring and stent expansion toward the side branch (SB) are associated with better results during provisional stenting of coronary artery bifurcation lesions, these techniques are technically challenging and often leave unopposed struts near the carina. Methods: The "Jail Escape Technique" (JET) is performed by passing the proximal tip of the SB wire between the main vessel (MV) stent struts and balloon before implantation, allowing the MV stent to push the SB wire against the distal part of the carina. The MV stent can then be deployed without jailing the SB wire. Distal SB access and strut distribution at the carina were tested in phantom and swine models. Stent distortion, dislodgement forces, and material damage were evaluated with tensile testing. Human feasibility was then tested on 32 patients. Results: Preclinical testing demonstrated that the SB wire was located at the most distal part of the carina and no strut malapposition at the carina was present after balloon inflation. Stent distortion, dislodgement forces, or material damage were not affected. JET was successfully performed in 30 of 32 patients. No major adverse cardiovascular events occurred in any patient at 6‐month follow‐up. Conclusion: The "JET" enables distal SB access and eliminates strut malapposition at the carina. Further studies with larger numbers of patients are needed to further investigate this technique.